Microwave assisted synthesis of quinoxaline derivatives - Lucas K. Beagle; Eric Horsting; Jacob Buechele; Judit K. Beagle (Results in Chemistry, 2023)
Substituted quinoxalines are known building blocks for compounds with pharmacological, agricultural, and material uses. Forming carbon-heteroatom bonds at the 2,3-positions on quinoxaline can be challenging. 2,3-chloroquinoxaline can undergo nucleophilic aromatic substitution however it must be in the presence of metal catalysts. A range of nucleophiles are investigated to showcase the broad range of potential substitution partners that can be incorporated effectively into the 2,3-disubstituted scaffold. This research focuses on a robust microwave-assisted one-pot procedure to gain efficient access to symmetrically 2,3-substituted quinoxalines without the use of a metal catalyst.